NEED ASSESSMENT OF HUMAN RESOURCES FOR RESEARCH AND INNOVATION PROFESSION IN SOCIAL SCIENCE; CASE STUDY OF DUHOK UNIVERSITY - AHMED, ARAZ SULAIMAN (Fırat Üniveristesi, 2019)
Bugün dünya tüm alanlarda hızla gelişiyor ve ilerliyor. İnsan, bu çarpıcı gelişmelerin merkezinde üretici ve yararlanıcı olarak yer almaktadır. Bu düşünceyle gelişmiş dünya ve gelişmekte olan dünya, insan kaynaklarını farklı derecelerde geliştirmek için on yıllardır çalışmakta. Buradaki araştırma problemi, günümüzdeki gelişmenin, dönemin temel unsurlarından biri olan pratik bilginin, insan kaynakları geliştirme ve modernizasyonu kavramına girdiği yenilikler, eğitimin gelişiminin temel taşı olarak ele alınmıştır. Bu nedenle, araştırma, insani gelişmenin doğal gelişimini ve boyutlarını, modern insani gelişme kavramı içinde ve geçmişten günümüze insan kaynakları ve yetkinliklerin yatırımına bir girdi olarak eğitimin önemine vurgu yaparak sunmayı amaçlamaktadır. İnsan kaynakları geliştirme yöntemleri, bireysel çalışanlara önem vermek veya onları modern yöntemlerle zenginleştirmek için eğitmektir. Bireysel bir çalışanın becerilerini ve yeteneklerini geliştirmek için eğitmektir. Çalışma, sosyal bilimlerde araştırma ve inovasyon için gerekli insan kaynakları ihtiyaçlarının bir değerlendirmesini yapmaktadır. Araştırma, Duhok Üniversitesi'nden elde edilen verilerin tüm üniversiteye uygulanabilecek şekilde fakülteler seçilerek anket aracılığıyla yürütülmüştür. Anketlerden elde edilen veriler, üniversitede ihtiyaç duyulan kaynaklar şeklindeki değişkenleri ve regresyon analizi ile aralarındaki bağlantıları elde etmek için analiz edilmiştir. Araştırma sonuçlarına göre bir dizi önerilerde bulunmuştur. Çalışmanın sonuçları, Duhok Devlet Üniversitesi'nin araştırma ve inovasyon faaliyetlerinin yaygınlaşmasına katkıda bulunacak operasyonel gelişime açısından faydalıdır. Anahtar Kelimeler: Değerlendirme, İhtiyaçlar, İnsan Kaynakları, Yenilik ve Bilimsel Araştırma

The world today is evolving and advancing rapidly in all areas. Human is at the heart of these dramatic developments. Human are the manufacturer and beneficiary of this development. The developed world and the developing world have been working for decades to develop their human resources to varying degrees. The research problem here focused on education as the cornerstone of development in the present age, when practical knowledge is one of the key elements, productivity became very important within the concept of human resources development and modernization. Therefore, the research aims to present and analyse the natural development and dimensions of human development, with emphasis on the importance of education as an input to the investment of human resources and competencies in the present within modern concept of human development. The modern method of human resources development is training to give individual employees or enrich them with skills. Skills are tool that through training to develop abilities of an individual employee. The study attempts to identify need assessment of human resources which is essential for research and innovation on social sciences. The research was conducted through a questionnaire issued by the University of Duhok by selecting a number of faculties of Duhok University, which can extract the results obtained from the research and apply them to the whole university. The data obtained from the survey was analysed by computer software in order to obtain the results using the links between the research variables and the regression analysis to understand the good ways in which university resource needs can be assessed. The research was reach a number of conclusions that explain the problem and the objectives of the study. The research was also provided a number of suggestions based on search results. From research point of view, this study was contributed to the development of Duhok government operations and to achieve useful benefits from the conclusion of research and suggestions. Keywords: Assessment, Needs, Human Resources, Innovation, and Scientific Research
Sosyal bilimlerde araştırma ve yenilik mesleğinde insan kaynaklarının değerlendirilmesi; Duhok Üniversitesi örnek olay incelemesi
Keywords: Eğitim ve Öğretim; İşletme